2019
DOI: 10.1016/j.omtn.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived miRNA-Containing Exosomes Induce Peritendinous Fibrosis after Tendon Injury through the miR-21-5p/Smad7 Pathway

Abstract: Following tendon injury, the development of fibrotic healing response impairs tendon function and restricts tendon motion. Peritendinous tissue fibrosis poses a major clinical problem in hand surgery. Communication between macrophages and tendon cells has a critical role in regulating the tendon-healing process. Yet, the mechanisms employed by macrophages to control peritendinous fibrosis are not fully understood. Here we analyze the role of macrophages in tendon adhesion in mice by pharmacologically depleting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 57 publications
4
116
0
Order By: Relevance
“…Tissue fibrosis is characterized as the up-regulation of profibrotic factors (e.g., TGF-β, CTGF) and ECM components (e.g., Fibronectin, Collagen type I) that destroys normal histological structures, ultimately leading to organ dysfunction 100 , 101 . Recently, Mφ-EVs have been implicated in the pathology of tissue fibrosis, as their administration restarts the profibrotic pathways after depletion of macrophages in mice 102 . Asbestos exposure is a major cause of several severe lung diseases such as malignant mesothelioma (MM), lung fibrosis (asbestosis), and bronchial carcinoma.…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…Tissue fibrosis is characterized as the up-regulation of profibrotic factors (e.g., TGF-β, CTGF) and ECM components (e.g., Fibronectin, Collagen type I) that destroys normal histological structures, ultimately leading to organ dysfunction 100 , 101 . Recently, Mφ-EVs have been implicated in the pathology of tissue fibrosis, as their administration restarts the profibrotic pathways after depletion of macrophages in mice 102 . Asbestos exposure is a major cause of several severe lung diseases such as malignant mesothelioma (MM), lung fibrosis (asbestosis), and bronchial carcinoma.…”
Section: Pathological Roles Of Mφ-evs In Diseasementioning
confidence: 99%
“…The fresh samples collected were performed for macroscopic evaluation, five independent samples from each group, using the adhesion grading score. 29 1) no adhesion tissue; 2) adhesion tissue can be separated by blunt dissection; 3) clear and sharp dissection is required, but less than 50% of the adhesion tissue is separated; 4) clear and sharp dissection is required to separate 51~97.5% of the adherent tissues; 5) clear and sharp dissection is needed, and eventually more than 97.5% of the adherent tissues could be separated.…”
Section: Animal Experimentsmentioning
confidence: 99%
“…28 In addition, our previous research showed that miR-21a-5p was abundant in macrophages, and the low expression of miR-21a-5p macrophage exosomes inhibited tendon adhesion. 29 Similarly, miR-21a-3p, as one member of miR-21 family, was reported to participate in nicotinestimulated macrophage exosome-induced atherosclerosis, 30 which is clearly inseparable from the course of fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of tenocytes in a number of in vitro and in vivo experimental models with EVs from various sources, e.g. plasma [ 14 ], adipose stem cells [ 15 ], tendon progenitors [ 16 ], macrophages [ 17 ], have demonstrated that signalling through EVs can modulate the expression of genes that regulate ECM synthesis and remodelling. Exosomes derived from tendon cells have also been reported [ 18 , 19 ]; and one study showed that tendon cell-derived exosomes induce the expression of tenogenic genes in bone marrow-derived mesenchymal stem cells in a TGFβ-dependent manner [ 19 ].…”
Section: Introductionmentioning
confidence: 99%